Genetic manipulation of sucrose-storing tissue to produce alternative products - Nell, Hanlie (Stellenbosch : University of Stellenbosch, 2008)
The main aim of the work presented in this dissertation was to explore the possibility to genetically manipulate the sucrose storing crops, sugarcane and sweet sorghum, to convert their sucrose reserves into higher-value alternatives. For the purpose of this study we focussed on fructans as alternative sucrose-based high-value carbohydrates, since these fructose polymers are of significant commercial interest. To investigate the technical feasibility of transforming sugarcane and sweet sorghum to produce this novel carbohydrate, we proposed to transfer the fructosyltransferase genes from Cynara scolymus into these plants by means of particle bombardment. In order to apply this technology to sweet sorghum, an in vitro culture system suitable for transformation had to be established. For this purpose an extensive screening process with different combinations of variables were conducted. Though the relationships between these variables proved to be complex, it was concluded that immature zygotic embryos could be used to initiate a genotype-independent totipotent regeneration system with a 65% callus induction rate, provided that initiation takes place during summer. Stable transformation and regeneration of these calli were however not successful and will have to be optimised to allow future applications. By introducing fructosyltransferase genes into sugarcane, we succeeded in transforming sugarcane into a crop that produces a variety of fructans of the inulintype. Low molecular weight (LMW) inulins were found to accumulate in the mature internodes of 42% of the transgenic sugarcane plants expressing the sucrose:sucrose 1-fructosyltransferase (1-SST) gene, and in 77% of the plants that incorporated both 1-SST and fructan:fructan 1-fructosyltransferase (1-FFT), while only 8% of these plants accumulated high molecular weight (HMW) inulins. Our results demonstrated that sugarcane could be manipulated to synthesise and accumulate fructans without the induction of phenotypical irregularities. Inulins with a degree of polymerisation up to 60 were found in sugarcane storage tissue. In these HMW inulin-producing plants, up to 78% of the endogenous sucrose in the mature sugarcane culm was converted to inulin. This enabled inulin accumulation up to 165.3 mg g-1 fresh weight (FW), which is comparable to that found in native plants. These transgenic sugarcane plants, therefore exhibit great potential as a future industrial inulin source. Fructan production was detected in all the sugarcane plant tissue tested, predominantly as 1-kestose. In contrast with the fact that fructan accumulation in leaves did not affect the endogenous sucrose concentrations in these organs, the sucrose content of mature internodes that accumulated high levels of 1-kestose was severely reduced. However, increases in total sugar content, in some instances up to 63% higher than control plants, were observed. This phenomenon was investigated with the use of radio-labelled-isotopes. An increase in the allocation of incoming carbon towards sucrose storage, resulting in higher carbon partitioning into both 1- kestose and sucrose, were detected in the culms of transgenic compared to control lines. This modification therefore established an extra carbohydrate sink in the vacuoles that affected photosynthate partitioning and increased total soluble sugar content. The data suggests that sucrose sensing is the main regulatory mechanism responsible for adapting carbon flow in the cells to maintain sucrose concentration.